Bourdieu and Literature - Speller, John R.W. (Author) (Open Book Publishers, 2011)
Bourdieu and Literature is a wide-ranging, rigorous and accessible introduction to the relationship between Pierre Bourdieu's work and literary studies. It provides a comprehensive overview and critical assessment of his contributions to literary theory and his thinking about authors and literary works. One of the foremost French intellectuals of the post-war era, Bourdieu has become a standard point of reference in the fields of anthropology, linguistics, art history, cultural studies, politics, and sociology, but his longstanding interest in literature has often been overlooked. This study explores the impact of literature on Bourdieu's intellectual itinerary, and how his literary understanding intersected with his sociological theory and thinking about cultural policy. This is the first full-length study of Bourdieu's work on literature in English, and it provides an invaluable resource for students and scholars of literary studies, cultural theory and sociology.